Lactation response of cross bred dairy cows fed on indigenously prepared rumen protected fat-A field trial - NAIK, P K; SAIJPAUL, S; SIROHI, A S; RAQUIB, M (The Indian Journal of Animal Sciences, 2011)
A field trial was conducted to study the effect of supplementation of an indigenously prepared rumen protected fat (PF) on lactation response in crossbred dairy cows. High yielding multiparous (2nd to 3rd lactation) crossbred cows (15) were randomly divided into 3 groups of 5 animals in each, based on parity, date of parturition and previous lactation milk yield. During early lactation i.e. up to 90 days of post partum period, the animals were offered 6.5 kg CM1, 25 kg green berseem and 2 kg wheat straw (WS) daily. During the mid lactation i.e. from 90 to 150 days post partum period, the feeding schedule was 6.5 kg CM2, 35 kg green maize and 1 kg WS daily. Besides, the animals in 3 groups were randomly supplemented without (control) or with 200 g RBO (RBO200) or 200 g PF (PF200) on fat equivalent basis. The CP and EE contents of the total ration during early (TMR1) and mid (TMR2) lactation were 16.2 and 3.5% , and 14.1 and 3.5%, respectively. In the treatment groups, due to the supplemental fat, the EE content of the TMR1 and TMR2 was 5.2% and 5.0%, respectively. There was consistently higher milk yield (MY) and 4% fat corrected milk yield (FCMY) in the PF200 group over the control and RBO200 group throughout the lactation period. During early lactation, the MY increased 3.2 kg/day (19.6%) and the FCMY increased 2.8 kg/day (22.3%) in the PF200 group over the control group. However, the RBO200 group had no beneficial effect on MY and FCMY over the control group. The milk composition (fat, SNF, protein and lactose) remained similar among the groups, but the total yield of milk fat, SNF and protein was higher in PF200 group over the control. The milk urea nitrogen (MUN)% was similar among the groups and was with in the normal range. During mid lactation, although the MY and FCMY in PF200 group were higher than the control group, it could not pass the statistical test and the RBO200 group had no effect on the MY and FCMY. Besides, both RBO200 and PF200 groups had no effect on the milk composition. The MUN% was also similar among the groups and was with in the normal range. In early lactation, the initial, final and changes in body weight (BW) and body condition score (BCS) were similar (P>0.05) among the groups. There was initial fall in both BW and BCS in all the groups followed by gradual recovery after the peak yield, however, the recovery of the BW and BCS in RBO200 and PF200 groups was better than the control group. Also, in the mid lactation, the initial, final and changes in BW and BCS were comparable (P>0.05) among the groups. The number of artificial inseminations required per conception in PF200 group (1.2) was lower than the RBO200 group (1.4), indicating better reproductive performance. Due to supplementation of the PF, there was net profit of Rs 34.50/cow/day over the control group during early lactation. It was concluded that the daily supplementation of 200 g PF (Ca-LCFA) increased MY (3.2 kg/day; 19.6%) and FCMY (2.8 kg/d; 22.3%) with improved reproductive performance and BCS in cross bred cows over the control group during early lactation, however, the supplementation had no significant beneficial effect in mid lactation.